Face Threatening Acts of the Main Character in â€œThe Half of itâ€ Movie - Kadek Gita Arya Cahyaningrum; Gede Primahadi Wijaya Rajeg; I Nyoman Tri Ediwan (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
This study analyzed face threatening acts (FTAs) used by the main character in the movie titled The Half of It, focusing on (i) the types of the FTAs and (ii) how the FTAs are used by the main character. The data came from all utterances (words, phrases, clauses, sentences) produced by the main character. A pragmatic theory of FTAs from Brown and Levinson was applied to analyze the data qualitatively. Four types of FTAs are found in this study. The first type is â€œthreatening the hearerâ€™s negative faceâ€, which was embedded in specific acts used by the main character, namely Suggestion, Threat, Reminding, Order, Warning, and Compliment. The second type is, â€œthreatening the speakerâ€™s negative faceâ€, which is followed by such acts as Response to the hearerâ€™s faux pas, Excuses, and Acceptance of offers. The third type is, â€œthreatening the hearerâ€™s positive faceâ€ with the acts of Criticism, Insults, Disagreement, Ridicule, Reprimand, Disapproval, Irreverence, Complaints, and Accusations. The last type of the FTAs is â€œthreatening the speakerâ€™s positive faceâ€ by using Confession, Emotion leakage, Physical control over the body, Apology, and Acting stupid. Finally, the FTAs enacted in the utterances of the main character are minimized by means of applying the politeness strategies. It has been discovered that the main character used the four types of politeness strategy that were positive politeness, negative politeness, bald on-record, and off-record strategy.